Khon tham phiphitthaphan / Chīwasit Bunyakīat bannāthikān ; phūkhīan, Panitā Sawāsī, Chīwasit Bunyakīat. - Panitā Sawāsī (ʻĒkkasān wichākān, 2014)
Research on local museums and local history in Thailand.